Association of Dietary Insulin Index and Dietary Insulin Load With Metabolic Health Status in Iranian Overweight and Obese Adolescents - Hajhashemy, Zahra; Mirzaei, Saeideh; Asadi, Ali; Akhlaghi, Masoumeh; Saneei, Parvane (Frontiers in Nutrition, 2022)
Background: Limited data are available on the association of dietary insulin load (DIL) and dietary insulin index (DII) with health status in pediatrics. We aimed to investigate the relation of DIL and DII with metabolic health status in Iranian overweight/obese adolescents. Methods: In this cross-sectional study, using a multistage cluster random-sampling method, 203 overweight/obese adolescents (aged 12 to <18 years) were included. A validated 147-item food frequency questionnaire (FFQ) was used for dietary intake assessment. Glycemic and lipid profile, blood pressure and anthropometrics indices were measured. Participants were categorized as metabolically healthy obese (MHO) or unhealthy obese (MUO) using two methods of International Diabetes Federation (IDF) and combination of IDF with Homeostasis Model Assessment Insulin Resistance (HOMA-IR). Results: According to IDF and IDF/HOMA-IR strategies, 38.9% (n=79) and 33.0% (n=67) of participants belonged to MUO category, respectively. After adjustments for potential confounders, subjects in the highest tertile of DIL in comparison with those in the bottom tertile had an odds of 8.44 (95%CI: 2.24-31.78) and 5.86 (95%CI: 1.39-24.58) for MUO based on IDF and IDF/HOMA-IR definitions, respectively. Moreover, after considering potential confounders, adolescents in the highest tertile of DII, compared to the lowest tertile, were respectively 6.93 (OR: 6.93; 95% CI: 2.59-18.57) and 5.26 (OR: 5.26; 95% CI: 1.85-14.97) times more likely to be MUO, based on IDF and IDF/HOMA-IR definitions. A Significant decreasing trend was observed for odds of MUO in tertiles of DIL and DII. Stratified analysis revealed that these associations were stronger in obese participants; in overweight subjects, the association was not independent from confounders. Conclusions: This population-based study revealed that higher DIL and DII were strongly related to increased odds of MUO in Iranian adolescents, especially in obese participants. Further investigations, especially with prospective design, are needed to affirm these findings.